Effect of magnetic field on haemodynamic perturbations in atherosclerotic coronary arteries. (17th February 2018) - Javadzadegan, Ashkan; Moshfegh, Abouzar; Behnia, Masud
Abstract: Haemodynamic perturbations including elevated blood viscosity, low and oscillatory shear stress are understood to be important pathogenic mediators in atherosclerosis. These haemodynamic abnormalities are influenced by the presence of a magnetic field. This study conducted computational fluid dynamics (CFD) analysis in 4 coronary artery models, derived from authentic human coronaries, with mild and moderate and severe stenosis severity. The aim was to investigate the effect of a static magnetic field of varying intensities on blood viscosity, areas of low wall shear stress (ALWSS), maximum wall shear stress (MWSS) and length and volume of flow recirculation zones. The results showed that the magnetic field results in both beneficial and detrimental changes in haemodynamics. The beneficial effects are lowered viscosity, decreased size of ALWSS and flow recirculation zones whereas the detrimental effect is increased MWSS. With increasing stenosis severity the effect of magnetic field becomes more prominent. An externally applied magnetic field can improve haemodynamics perturbations in human coronary arteries, especially in the setting of moderate-to-severe stenosis severity.